Analysis of dynamics of the medcine list in the government program «available medicines» for treatment of bronchial asthma - I. A. Kostiuk (The State Expert Center of the Ministry of Health of Ukraine, 2019)
The problem of accessibility for socially significant goods for the population, among which the most important place occupy medicines in Ukraine, is very acute today. In this regard, the need for specific state interference through regulatory processes becomes relevant. One of the priority directions for increasing the availability of medicines is the Government of Ukraine has recognized reimbursement. The mechanism of full or partial payment of the cost of medicines used to counteract most socially significant diseases. One of these diseases is bronchial asthma (BA), since it affects all age groups of the population, and with ineffective control of the disease, the quality of life of patients is significantly reduced. The aim of the work is to study the range of medicines for the treatment of BA, included in the Government program «Accessible medicines» for the period 2017-2019 years. From April 1, 2017 to July 1, 2019, the Ministry of Health of Ukraine issued five orders, which approved the Register of medicines, the cost of which is subject to reimbursement. In the study analyzed all editions of the Register and found that with each update, the number of trade names (TN) of the medicines increased: for the treatment of cardiovascular diseases - by 56%, diabetes - by 92%, and BA - by 133%. During the 2017-2019 years, the number of international non-proprietary names (INNs) for the treatment of BA also increased: 3 times Beclomethasone, Budesonide 3.5 times, and Salbutamol is almost 2 times. Also, found that 87% of TN are imported and only 13% - domestic. Total of medicines for the treatment of asthma, the value of which is refundable imports 6 countries, the main segment of which is formed by Spain (31%) and Sweden (23%). The analysis of the size and amount of rejection and the amount of the surcharge for packaging allows us to establish that the percentage of medicines without an additional payment is approximately up to 50%. At 75% of the medicines for the treatment of BA, the amount of packing surcharge with each edition of the Register of medicines subject to reimbursement was increased by 2 medicines (Beckhazon-eco 100 mcg/dose and 250 mcg/dose) and 1 medicine (Budesonide-inteli 200 mcg/dose) - decreased 1 medicine (Budesonide-inteli 200 mcg/dose) subject to partial compensation only once. The conducted studies allow us to conclude that there is a need to improve the assortment policy in order to provide the pharmaceutical market with the available and necessary domestic medicines, in accordance with the needs of the population and the standards for the treatment of BA.